Implementation of Guided Imagery Relaxation Therapy Application on Blood Pressure Changes in Hypertension Patient - Ramanda, Nuri; Triguna, Yudi; Adini, Syaukia; Asep Riyana (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose: The purpose of this case study is to describe the nursing care process for patients with hypertension through the application of guided imagery relaxation therapy and its effect on changes in blood pressure. Methods: This scientific paper uses a qualitative design with a case study approach conducted on two hypertensive patients at Khz Mushtafa Hospital. Data were collected through interviews, observations, and physical examinations. Guided imagery relaxation therapy was implemented once daily in the afternoon for 15–20 minutes over three consecutive days. Results: The results of the case study showed a decrease in blood pressure in both patients after the application of guided imagery relaxation therapy. Patient 1 experienced a reduction in systolic blood pressure of 38 mmHg and diastolic blood pressure of 12 mmHg. Patient 2 showed a decrease in systolic blood pressure of 20 mmHg and diastolic blood pressure of 15 mmHg. Conclusions: The conclusion of this case study demonstrates that guided imagery relaxation therapy is effective in lowering blood pressure in patients with hypertension. It is expected that hypertensive patients can perform guided imagery relaxation therapy routinely and regularly as a complementary nursing intervention to help improve blood pressure control and achieve values closer to normal.